2018
DOI: 10.1016/j.expneurol.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal erythropoietin mitigates impaired gait, social interaction and diffusion tensor imaging abnormalities in a rat model of prenatal brain injury

Abstract: Children who are born preterm are at risk for encephalopathy of prematurity, a leading cause of cerebral palsy, cognitive delay and behavioral disorders. Current interventions are limited and none have been shown to reverse cognitive and behavioral impairments, a primary determinant of poor quality of life for these children. Moreover, the mechanisms of perinatal brain injury that result in functional deficits and imaging abnormalities in the mature brain are poorly defined, limiting the potential to target in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 114 publications
(204 reference statements)
4
64
0
Order By: Relevance
“…Consistent with clinical data, the preclinical findings reported here reaffirm the concept that chorioamnionitis concomitant with placental insufficiency results in dynamic, multifactorial, and permanent changes to the CNS culminating in functional deficits in mature rats. Indeed, this prenatal insult causes significant chronic behavioral, social, executive function, and gait deficits in adult rats, similar to those observed in children with CP ( 46 , 62 , 71 ). This model that incorporates intrauterine chorioamnionitis is one of very few preclinical models to induce persistent gait and neurocognitive deficits in the mature CNS ( 40 , 70 ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent with clinical data, the preclinical findings reported here reaffirm the concept that chorioamnionitis concomitant with placental insufficiency results in dynamic, multifactorial, and permanent changes to the CNS culminating in functional deficits in mature rats. Indeed, this prenatal insult causes significant chronic behavioral, social, executive function, and gait deficits in adult rats, similar to those observed in children with CP ( 46 , 62 , 71 ). This model that incorporates intrauterine chorioamnionitis is one of very few preclinical models to induce persistent gait and neurocognitive deficits in the mature CNS ( 40 , 70 ).…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, through EPO and MLT together, it may be possible to cumulatively preserve more axon-myelin structural units, including those in major cerebral white matter and corticospinal tracts, by inhibiting detrimental protease expression, preserving structural connectivity, and restoring inhibitory neural networks. Indeed, it is through this action on structural and functional connectivity, neural conduction, and excitatory/inhibitory balance of fundamental circuitry that this combination of therapy likely improves motor and cognitive function into early adulthood (P90) following prenatal injury ( 46 48 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using DTI in children with hydrocephalus have shown alterations in white matter microstructural integrity ( Mangano et al, 2016 ; Zhao et al, 2016 ), similar to what we have shown here in toddler-equivalent P21 vehicle-treated CAM-IVH rats. In preclinical studies, extended neonatal EPO treatment mitigated widespread DTI abnormalities in white and gray matter ( Robinson et al, 2016 , 2017 ). Here, we showed that sustained neonatal treatment with EPO+MLT normalizes subacute DTI changes at 3 weeks after CAM-IVH.…”
Section: Discussionmentioning
confidence: 99%
“…This process of random assignment followed by correlational analysis was repeated 5 times. Only those ROI that showed significant Pearson correlation on all 5 random assignments AND showed repair of EPO at P30 were considered robust ( 41 ). The correlations for a representative random assignment are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%